Body image discontentment among head and neck cancer patients in Visakhapatnam district: An empirical study (Research, Society and Development, 2024)
Head and neck cancers, which comprise tumours of the oral cavity, throat, nasal cavity, and thyroid, pose substantial physical and psychological issues. These tumours frequently require harsh therapies such as surgery, radiation therapy, and chemotherapy, which can result in apparent changes in appearance and physical function. As a result, patients are frequently subjected to body image distress, low self-esteem, and overall unhealthy psychological well-being. This study aims to investigate head and neck cancer patients' self-perceptions and body image problems, with an emphasis on feelings of self-consciousness, physical attractiveness, and general body dissatisfaction amongst head and neck cancer out patients undergoing treatment in HCG cancer hospital in Visakhapatnam. This study was conducted on 50 head and neck cancer outpatients undergoing treatment at an oncology centre Healthcare Global Enterprises ltd (HCG) hospital Visakhapatnam during the period of (May 2023 to June 2023) who were willing to participate in the study and were 20 years of age and above. An interview schedule was prepared by the researcher and administered to the patients comprising section A (questions pertaining to the demographic and clinical details of the patient), section B (modified 6 item Body Image Scale). Majority of the patients were male (62%) while female constituted 38% with the majority aged between 20- 39 years (61%) and the most common cancer being that of oral cavity (58%). The findings reveal a sizable proportion of respondents reporting feeling self-conscious and less physically attractive as a result of their sickness or treatment. Many individuals are dissatisfied with their appearance and overall body image, with a significant percentage reporting that these issues interfere with their social relationships and sense of wholeness. These findings highlight the need of addressing psychological and emotional support in the treatment and care of head and neck cancer patients. Integrating mental health and body image counselling into cancer treatment programmes has the potential to greatly improve patients' overall well-being and quality of life.